Penggunaan Sonkeigo dan Kenjougo Dalam Al-Qur'an Terjemahan Bahasa Jepang Surat Maryam - Abdillah, Aria; Suryadi, Yudi; Kurniawan, Eko (KIRYOKU, 2021)
The Japanese language has a variety of respectful languages that are used in Japanese social ethics. This variety of respectful language is known as keigo. Keigo is a speech level that functions to express respect for the speech partner. The expression to express respect is not only used to fellow human beings, but also Allah as the Creator. The purpose of this research was to determine the types of sonkeigo and kenjougo in the Japanese translation of the Qur'an, to describe the word-formation process and the grammatical meaning. This research is qualitative research by applying a qualitative descriptive method. The method of collecting data using a listening method with the writing technique. The data source in this research is the Japanese translation of the Qur'an surah Maryam chapter 4 to 32. In the data source, 14 data were found which is divided into 10 sonkeigo data and 4 kenjougo data. Based on the results of data analysis, it was found that the sonkeigo word-formation process used the ~rareru pattern with 7 data, the o~ni naru pattern with 1 data, and the o~kudasai pattern with 2 data. The kenjougo word-formation process used a special form of verb patterns with 3 data and an o~suru pattern with 1 data. The sonkeigo speech level is used in the context of Allah's actions, Allah's decree to Zakaria, Maryam, and Isa. The kenjougo speech level is used in the context of Zakaria's pray to Allah and Allah's decree to Maryam which was conveyed through Jibril.